Regional Technolgy Policy and Factors Shaping Local Innovation Networks in Small German Cities - Andrea Gebauer; Chang Woon Nam; Rüdiger Parsche (European Regional Science Association (ERSA), 2003)
Local innovation networks have been considered to be particularly important to innovation and technological change and to the growth prospects of regions and cities in Germany. Accordingly, innovation is a process that results from various (economic and social) interactions of different institutions located in a given region. Consequently, when analysing the local (or regional) innovation system, one should not only investigate the (horizontal and vertical) relations among firms but also the contacts with universities and other research institutions. Furthermore, the role of government agencies and interest groups that provide financial support as well as commercial and technical information should also be taken into account in the context of the regional innovation system. However, the review of relevant theoretical and empirical investigations related to the German experience shows that such innovation and R&D cooperation networks appear to be less significant than expected. In particular those high-tech firms in small-sized German cities have a direct access to the international innovation network, which quite often has made a more crucial contribution to their business performances than the regional and national ones have done. In general various regional technology policy measures adopted in German states (provision of research infrastructure, establishment of technology centres, innovative SME support programmes, etc.) have been more successful in already economically better-off large cities but failed to establish a significant intra-technological cooperation among partners in the rather less-developed areas which lack sufficient know-how, a socio-cultural and institutional infrastructure and a certain degree of entrepreneurial tradition. Apat from offering a critical review of relevant theoretical and empirical research, this study introduces the present regional technology and R&D promotion policies in German states and examines the distinctive characteristics of the local innovation system, emphasising the experiences of two small cities, Landshut and Bochum.
Keywords: 330